2017
DOI: 10.3389/fneur.2017.00173
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Loss in Older Adults Is Associated with Impaired Spatial Navigation: Data from the Triangle Completion Task

Abstract: BackgroundVestibular inputs have been shown to play a critical role in spatial navigation. In this study, we sought to evaluate whether vestibular loss due to aging contributes to impaired spatial navigation as measured by the triangle completion task (TCT).Materials and methodsWe recruited three types of participants: young controls <55 years of age, older controls ≥55 years of age, and older patients from a Neurotology Clinic with evidence of vestibular physiologic impairment but who did not have any known v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 33 publications
2
71
0
4
Order By: Relevance
“…One recent study in community-dwelling adults found a significant association between vestibular function and tests of visuospatial cognitive ability ( 4 ). Studies using the triangle completion task (TCT) have shown that vestibular function (both otolith and canal) contributes to performance on a dynamic spatial navigation task ( 5 , 6 ). Furthermore, patients with bilateral vestibular loss were shown to have lower hippocampal volumes and impaired spatial memory and navigation as assessed with a virtual maze test ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study in community-dwelling adults found a significant association between vestibular function and tests of visuospatial cognitive ability ( 4 ). Studies using the triangle completion task (TCT) have shown that vestibular function (both otolith and canal) contributes to performance on a dynamic spatial navigation task ( 5 , 6 ). Furthermore, patients with bilateral vestibular loss were shown to have lower hippocampal volumes and impaired spatial memory and navigation as assessed with a virtual maze test ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Objektive Messergebnisse zu Ganganomalien sind die Ganggeschwindigkeit, das Tandemgehen und Indizes wie der Dynamic-Gait-Index und die funktionelle Gangbeurteilung [86]. Schwindelbedingte Behinderungen können beispielsweise mit Patienten-Fragebögen wie dem Dizziness Handicap Inventory genauer ermittelt werden [87]. Stürze können auf der Basis der Anzahl der Stürze in einem bestimmten Zeitraum quantifiziert oder anhand von Patienten-Fragebögen wie dem Falls Efficacy Scale [88] näher bestimmt werden.…”
Section: Symptomeunclassified
“…Recent evidence from neuroimaging studies indicates that signatures of grid-cell-like activity in human entorhinal cortex are reduced in old age, and this reduction is associated with larger path integration errors (Stangl et al, 2018). Certain aspects of the vestibular system also deteriorate with age (for a review, see Allen et al, 2016), and vestibular loss affects path integration performance (Glasauer et al, 2002;Xie et al, 2017). These findings support the possibility that an increase in noise on a neuronal level, possibly from a loss of the signal-to-noise ratio from degrading circuitry in the grid cell or the vestibular system may be responsible for deficient computations of pose in old age.…”
Section: Discussionmentioning
confidence: 99%